Data for: Abundance of short- and long-tongued bees, and their impact on red clover seed production in four cultivars grown across a large latitude range - Svensson, Kajsa; Hederström, Veronika; Valentin, Ida; Lindholm, Sara; Öhlund, Linda; Larsson, Mattias C.; Lankinen, Åsa (Swedish University of Agricultural Sciences, 2026)
The aim of this study was to investigate how short- and long-tongued bees (bumblebees and honeybees) affect seed production in different cultivars of red clover, focusing on tetraploid cultivars.

The study includes two experiments. In the first one, data were collected from field trials at six different sites (belonging to Lantmännen) distributed in southern and northern Sweden over two years. The data from this experiment include seed yield, seed set, abundance of short- and long-tongued bees and seed-eating weevils, and plant traits (flower head density and number of florets per flower head) from one diploid and three tetraploid red clover cultivars.

The second experiment was a cage study where seed yield from tetraploid red clover was evaluated from cages with different densities of the short-tongued bumblebee Bombus terrestris, and compared with seed yield from an open plot adjacent to the cages. This study was conducted in farmers' fields in southern and northern Sweden over two years.

Syftet med denna studie var att undersöka hur kort- och långtungade bin (humlor och honungsbin) påverkar fröavkastning hos olika sorter av rödklöver, med fokus på tetraploida sorter.

Studien består av två olika experiment. I det ena experimentet samlades det in data från fält på sex olika platser (Lantmännens forskningsstationer) utspridda i södra och norra Sverige över två år. Här samlades det in data på fröskörd, frösättning, förekomst av pollinerande bin och skadevivlar, och växtegenskaper (densitet av blomhuvuden samt antal småblommor per blomhuvud) från en diploid samt tre tetraploida rödklöversorter.

Det andra experimentet bestod av ett burförsök. Här undersöktes hur fröskörden i tetraploid rödklöver påverkas av olika densiteter av den korttungade humlan Bombus terrestris i burar jämfört med öppen pollinering från odlarfält i södra och norra Sverige under två år.
Data för: Abundance of short- and long-tongued bees, and their impact on red clover seed production in four cultivars grown across a large latitude range
Keywords: seed set; seed yield; ploidy level; red clover; rödklöver; bumblebees; humlor; seed production; fröproduktion; pollinators; pollinerare; honeybees; honungsbi; Bombus terrestris; mörk jordhumla; Trifolium pratense; Protapion trifolii; Apis mellifera; Protapion apricans; Bombus sp.; Protapion assimile; Ecology; Ekologi; Agricultural Science; Jordbruksvetenskap; Environmental Sciences and Nature Conservation; Miljö- och naturvårdsvetenskap